2018
DOI: 10.1371/journal.pone.0203951
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the use of complete denture adhesives on microbial adhesion and biofilm formation by single- and mixed-species

Abstract: ObjectivesTo verify whether the Ultra Corega Cream and Corega Strip Denture Adhesive adhesives interfere in the microbial adhesion and biofilm formation by Candida albicans and Lactobacillus casei in single- and mixed-species settings, and observe whether synergistic or antagonistic relationships between these species occur.MethodsSpecimens made from heat-polymerized acrylic resin (Lucitone 550) were fabricated (n = 144) with a circular shape and standardized roughness (3.0 μm ±0.3 Ra) and were divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In fact, C. albicans biofilm formation by (single-and mixed-species) was higher on the strip adhesive. The authors did not observe any relations of synergism or antagonism between the two microorganisms [103].…”
Section: Mixed Candida Spp/bacteria Biofilms: Features Pathogenicitmentioning
confidence: 82%
“…In fact, C. albicans biofilm formation by (single-and mixed-species) was higher on the strip adhesive. The authors did not observe any relations of synergism or antagonism between the two microorganisms [103].…”
Section: Mixed Candida Spp/bacteria Biofilms: Features Pathogenicitmentioning
confidence: 82%
“…According to various laboratory studies, C. albicans is the most frequently isolated strain that can adhere and form biofilms on the oral mucosa and subsequently cause denture stomatitis [ 22 , 23 ]. Over the decades, many efforts have been made to improve the material, the curing techniques, and the processes used for fabricating denture bases [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, there is an association between the characteristics of the denture acrylic surface and the amount of Candida colonization, followed by biofilm formation [ 10 , 11 ]. Other studies have also confirmed that surface roughness, porosity, and permeability can affect Candida colonization and biofilm formation on the removable denture acrylic surface [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…After incubation (37° C for 16 hours), the cultures were diluted 1:10 in TYE medium + 1% glucose and the initial optical density (OD) at 540nm was read in a spectrophotometer (CMC Laboratório Ltda., Brazil). The period corresponding to the midlog growth phase was approximately 8 h with OD 540nm = 1.07(±0.07) and microbial concentration of 2.31×10 7 (±3.55×10 6 ) CFU/mL [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The solution was centrifuged (4°C, 4000RPM, for 10 minutes—Centrifuge 5810R, Eppendorf, Hamburg, Germany) and the supernatant (clarified saliva) was filtered using a 0.22μm polyethersulfone membrane filter (Rapid Flow, Nalgene, Thermo Fisher Scientific, Waltham, Massachusetts, USA). Aliquots of saliva were kept at -80°C until use [ 36 ].…”
Section: Methodsmentioning
confidence: 99%